Real-world effectiveness of 8-week treatment with ledipasvir/sofosbuvir in chronic hepatitis C - Buggisch, Peter; Pathil-Warth, Anita (Journal of hepatology, 2018)
Background & Aims Ledipasvir/sofosbuvir (LDV/SOF) for 8 to 24weeks is approved for the treatment of chronic hepatitis C virus infection (HCV). In the ION-3 study, 8weeks of LDV/SOF was non-inferior to 12weeks in previously untreated genotype 1 (GT1) patients without cirrhosis. According to the Summary of Product Characteristics (SmPC), 8-week treatment may be considered in naïve non-cirrhotic GT1-patients. However, there are only limited data on the effectiveness of an 8-week regimen of LDV/SOF under real-world conditions. The aim of the present study was to characterise patients receiving 8 weeks of LDV/SOF compared to those receiving 12 weeks of LDV/SOF, and to describe therapeutic outcomes in routine clinical practice. Methods The German Hepatitis C-Registry is a large national real-world cohort that analyses effectiveness and safety of antiviral therapies in chronic HCV. This data set is based on 2,404 patients. Treatment with SOF/LDV (without RBV) for 8 or 12weeks was initiated on or before September 30, 2015. Results Overall, 84.6% (2,034/2,404) of the safety population (intention-to-treat-1 [ITT1]) and 98.2% (2,029/2,066) of the per protocol (PP) population achieved sustained virological response at week 12 (SVR12). In the 8-week group, 85.1% (824/968) of ITT1 and 98.3% (821/835) of PP patients achieved SVR12, while in the 12-week group, 85.5% (1,210/1,415) of ITT1, and 98.1% (1,208/1,231) of PP patients achieved SVR12. When treated according to the SmPC, 98.7% (739/749) of the patients achieved SVR12 (PP). Relapse was observed in 9.5% (2/21) of cirrhotic patients treated for 8weeks (PP). Conclusions Under real-world conditions a high proportion of eligible patients receiving 8-week LDV/SOF treatment achieved SVR12. Relapse occurred more frequently in patients who did not meet the selection criteria according to the SmPC. Lay summary In a large real-world cohort of patients mainly treated by physicians in private practice in Germany, shorter HCV treatment (8-week) resulted in equivalent cure rates to 12-week treatment in genotype 1 HCV-infected patients. Thus, shorter treatment can be recommended in these patients which would substantially reduce costs of therapy. Clinical Trial number: DRKS00009717 (German Clinical Trials Register, DRKS)